Logichart: A Prolog Program Diagram and its Layout - Adachi, Yoshihiro; Furusawa, Yudai (Electronic Communications of the EASST, 2007)
Abstract: The layout of Logichart diagrams is first discussed. The layout condition is formalized with a layout constraint (expressions of equalities and inequalities) of tree-structured diagrams. Next, a cell placement that gives the minimum-area layout under a specific layout constraint is presented. A Logichart attribute graph grammar is then formalized. This grammar is underlain by a neighborhood controlled embedding (NCE) graph grammar whose productions are defined in order to formalize the graph-syntax rules of Logichart diagrams. Semantic rules attached to the grammar's productions are defined in such a way that they can extract the layout information needed to display a Logichart diagram by means of the attributes attached to the nodes of the graphs derived by the grammar. The semantic rules are formalized so as to obtain the Logichart diagrams of the minimum area under the above layout constraint.